Hidden Holocene Slip Along the Coastal El Yolki Fault in Central Chile and Its Possible Link With Megathrust Earthquakes. Issue 7 (9th July 2019) - Melnick, Daniel; Hillemann, Christian; Jara‐Muñoz, Julius; Garrett, Ed; Cortés‐Aranda, Joaquín; Molina, Diego; Tassara, Andrés; Strecker, Manfred R.
Abstract: Megathrust earthquakes are commonly accompanied by increased upper‐plate seismicity and occasionally triggered fault slip. In Chile, crustal faults slipped during and after the 2010 Maule (M8.8) earthquake. We studied the El Yolki fault (EYOF), a transtensional structure midways the Maule rupture not triggered in 2010. We mapped a Holocene coastal plain using light detection and ranging, which did not reveal surface ruptures. However, the inner‐edge and shoreline angles along the coastal plain as well as 4.3‐ to 4.0‐ka intertidal sediments are back‐tilted on the EYOF footwall block, documenting 10 m of vertical displacement. These deformed markers imply 2‐mm/year throw rate, and dislocation models a slip rate of 5.6 mm/year for the EYOF. In a 5‐m‐deep trench, the Holocene intertidal sediments onlap to five erosive steps, interpreted as staircase wave‐cut landforms formed by discrete events of relative sea level drop. We tentatively associated these steps with coseismic uplift during EYOF earthquakes between 4.3 and 4.0 ka. The Maule earthquake rupture may be subdivided into three subsegments based on coseismic slip and gravity anomalies. Coulomb stress transfer models predict neutral stress changes at the EYOF during the Maule earthquake but positive changes for a synthetic slip distribution at the central subsegment. If EYOF earthquakes were triggered by megathrust events, their slip distribution was probably focused in the central subsegment. Our study highlights the millennial variability of crustal faulting and the megathrust earthquake cycle in Chile, with global implications for assessing the hazards posed by hidden but potentially seismogenic coastal faults along subduction zones. Key Points: Geomorphology and paleoseismic trenching suggest Holocene slip along El Yolki fault in Central Chile despite absence of surface ruptures A 4.3‐ka sequence of intertidal sediments has been uplifted 10 m along the footwall fault block Crustal faulting may be triggered by megathrust events with slip distribution different from the last M8.8 earthquake in 2010